2008
DOI: 10.1038/embor.2008.37
|View full text |Cite
|
Sign up to set email alerts
|

Synoviolin promotes IRE1 ubiquitination and degradation in synovial fibroblasts from mice with collagen‐induced arthritis

Abstract: The E3 ubiquitin ligase synoviolin (SYVN1) functions as an anti-apoptotic factor that is responsible for the outgrowth of synovial cells during the development of rheumatoid arthritis. The molecular mechanisms underlying SYVN1 regulation of cell death are largely unknown. Here, we report that elevated SYVN1 expression correlates with decreased levels of the protein inositol-requiring enzyme 1 (IRE1)-a pro-apoptotic factor in the endoplasmic reticulum (ER)-stress-induced apoptosis pathway-in synovial fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 18 publications
6
80
1
Order By: Relevance
“…This conclusion is validated by the following observations: (i) Conditional deletion of Hrd1 specifically in B-cell lineage results in reduced mature B cells in the peripheral lymphoid organs; (ii) Hrd1-deficiency sensitizes Fas-mediated activation-induced B-cell death, which can be largely Hrd1 functions as a critical regulator in protecting B cells from AICD, based on our observation that apoptosis in Hrd1 KO peripheral B cells upon antigenic stimulation was significantly increased. Fas was up-regulated at both the mRNA and protein level, initially suggesting that Fas expression might be indirectly induced upon increase of Hrd1 substrates, such as p53 or IRE1α (27,30). However, we did not detect a significant increase in the p53-target genes PUMA and p21 in activated Hrd1 KO peripheral B cells compared with WT.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…This conclusion is validated by the following observations: (i) Conditional deletion of Hrd1 specifically in B-cell lineage results in reduced mature B cells in the peripheral lymphoid organs; (ii) Hrd1-deficiency sensitizes Fas-mediated activation-induced B-cell death, which can be largely Hrd1 functions as a critical regulator in protecting B cells from AICD, based on our observation that apoptosis in Hrd1 KO peripheral B cells upon antigenic stimulation was significantly increased. Fas was up-regulated at both the mRNA and protein level, initially suggesting that Fas expression might be indirectly induced upon increase of Hrd1 substrates, such as p53 or IRE1α (27,30). However, we did not detect a significant increase in the p53-target genes PUMA and p21 in activated Hrd1 KO peripheral B cells compared with WT.…”
Section: Discussioncontrasting
confidence: 48%
“…S5 E and F), further confirming that Hrd1 protects B cells from AICD independent of UPR response. We have recently discovered that Hrd1 suppresses ER-stress-induced cell death through targeting the downstream ER-stress sensor IRE1α for ubiquitination and degradation (27,28). However, further deletion of IRE1α in Hrd1 KO mice could not rescue the reduction in the peripheral B cells in spleen (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also plays a crucial role in the pathogenesis of arthropathy and liver cirrhosis/fibrosis (Amano et al 2003;Hasegawa et al 2010). Although Hrd1 was initially characterized as an E3 ubiquitin ligase controlling ERassociated degradation (ERAD), recent reports demonstrate that Hrd1 can also control the turnover of non-ERAD substrates such as p53, IRE1, and Nrf1, a member of the cap'n'collar (CNC) transcription factor family (Yamasaki et al 2007;Gao et al 2008;Steffen et al 2010;Tsuchiya et al 2011). In addition to the UPR, reactive oxygen species (ROS) have been shown to play a major role in the pathogenesis of liver cirrhosis (Lotersztajn et al 2005;Wynn and Ramalingam 2012).…”
mentioning
confidence: 99%
“…3B). It has been shown that the ERresident ubiquitin ligase Hrd1 targets BLIMP-1 for ubiquitination and degradation in dendritic cells (18) and also targets IRE-1a (18,19), and hence we examined whether this pathway could operate downstream of CD40 engagement in B cells. We found that Hrd1 transcripts were higher in WT B cells than in CD40 2/2 B cells, and that Hrd1 was induced when WT B cells were treated with anti-CD40 Ab for 24 h (Fig.…”
Section: Cd40 Ligation Induces Hrd1 That Targets Blimp-1 and Ire-1a Pmentioning
confidence: 99%